Abordagem de leitura de texto em imagens provenientes de redes sociais para ganho em disponibilidade de dados - FERREIRA NETO, Luiz Cortinhas (Universidade Federal do Pará, 2018)
This work aims to propose a methodological adaptation in the process of social network analisys, based on the inclusion of text extracted from images that are obtained from the social networks themselves. Highly important for market intelligence, product analysis, CRM and SCRM processes, since these are market trends used by large companies, thus, promotes financial and research incentives. The adaptation proposed in here has its importance based on data availability, which has become increasingly restricted, thanks to the use of APIs, interfaces of data access management where, in several different ways, each social network limits the data query, either by type of data, quantity or collected window. This research intends to prove, through case studies, that there is relevant information gain to sentiment analyses process when textual data derived from images are used.